Interleukin-11 binds specific EF-hand proteins via their conserved structural motifs. Issue 1 (2nd January 2017) - Kazakov, Alexei S.; Sokolov, Andrei S.; Vologzhannikova, Alisa A.; Permyakova, Maria E.; Khorn, Polina A.; Ismailov, Ramis G.; Denessiouk, Konstantin A.; Denesyuk, Alexander I.; Rastrygina, Victoria A.; Baksheeva, Viktoriia E.; Zernii, Evgeni Yu.; Zinchenko, Dmitry V.; et al.
Abstract : Interleukin-11 (IL-11) is a hematopoietic cytokine engaged in numerous biological processes and validated as a target for treatment of various cancers. IL-11 contains intrinsically disordered regions that might recognize multiple targets. Recently we found that aside from IL-11RA and gp130 receptors, IL-11 interacts with calcium sensor protein S100P. Strict calcium dependence of this interaction suggests a possibility of IL-11 interaction with other calcium sensor proteins. Here we probed specificity of IL-11 to calcium-binding proteins of various types: calcium sensors of the EF-hand family (calmodulin, S100B and neuronal calcium sensors: recoverin, NCS-1, GCAP-1, GCAP-2), calcium buffers of the EF-hand family (S100G, oncomodulin), and a non-EF-hand calcium buffer (α-lactalbumin). A specific subset of the calcium sensor proteins (calmodulin, S100B, NCS-1, GCAP-1/2) exhibits metal-dependent binding of IL-11 with dissociation constants of 1–19 μM. These proteins share several amino acid residues belonging to conservative structural motifs of the EF-hand proteins, 'black' and 'gray' clusters. Replacements of the respective S100P residues by alanine drastically decrease its affinity to IL-11, suggesting their involvement into the association process. Secondary structure and accessibility of the hinge region of the EF-hand proteins studied are predicted to control specificity and selectivity of their binding to IL-11. The IL-11 interaction with the EF-hand proteins is expected to occur under numerous pathological conditions, accompanied by disintegration of plasma membrane and efflux of cellular components into the extracellular milieu.